2017
DOI: 10.1080/03071022.2018.1393997
|View full text |Cite
|
Sign up to set email alerts
|

‘It was better when it was worse’: blue-collar narratives of the recent past in Belgrade

Abstract: Based on oral history research conducted among networks of blue-collar workers in Belgrade, Serbia, this article develops three interrelated arguments regarding workers' appraisals of the recent past (1980-2014). Firstly, although the tumultuous years of late socialism and post-socialism in Serbia have been represented by scholars as a series of ruptures, I suggest that for blue-collar workers the boundaries between socialism and post-socialism and pre-conflict and wartime eras are blurry. Secondly, despite th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Another aspect that appeared frequently during the focus groups is nostalgia. Researchers of the post-Yugoslav space have encountered this time and again: the socialist past is seen by focus group participants as a kind of lost paradise (Petrović 2010; Kojanić 2015; Archer 2018). This means that researchers must peel back several layers while taking care not to impose any particular view on the focus group participants.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect that appeared frequently during the focus groups is nostalgia. Researchers of the post-Yugoslav space have encountered this time and again: the socialist past is seen by focus group participants as a kind of lost paradise (Petrović 2010; Kojanić 2015; Archer 2018). This means that researchers must peel back several layers while taking care not to impose any particular view on the focus group participants.…”
Section: Discussionmentioning
confidence: 99%
“…To the major disappointment of East Germans, the expected change did not bring about the 'capitalist paradise', but an extremely competitive society they were not accustomed to, with high unemployment, low salaries and the feeling of being second -rate citizens. All this created a situation where an important part of East German society still believes that 'everything was better back when everything was worse' (Archer 2018, Figus -Pisanuello -Mustica 2018Stone 2017).…”
Section: Specifics Of Ostalgy In the Former Gdrmentioning
confidence: 99%
“…Низ студија претежно квалитативног типа (Jansen, 2005;Volčič, 2007;Palmberger, 2008;Velikonja, 2010;Petrović, 2010;Kuljić, 2011;Bošković, 2013;Spaskovska, 2017;Popović, 2017;Archer, 2018) показао је да су успомене на живот у социјалистичкој Југославији веома присутне код становника свих бивших југословенских земаља (мада не у једнакој мери) и да попримају одлике југоносталгије. Тако су налази једног социолошког истраживања из 2011. године указали на постојање југоносталгије у савременој Србији (Spasić, 2012;Spasić & Birešev, 2012).…”
Section: теоријско-хипотетички оквирunclassified
“…A number of predominantly qualitative studies (Jansen, 2005;Volčič, 2007;Palmberger, 2008;Velikonja, 2010;Petrović, 2010;Kuljić, 2011;Bošković, 2013;Spaskovska, 2017;Popović, 2017;Archer, 2018) showed that the memories of life in socialist Yugoslavia are very vivid among the inhabitants of all former Yugoslav countries (though not equally) and that they take on the characteristics of Yugo-nostalgia. Thus, the findings of a sociological research from 2011 pointed to the existence of Yugo-nostalgia in contemporary Serbia (Spasić, 2012;Spasić & Birešev, 2012).…”
Section: The Theoretical and Hypothetical Frameworkmentioning
confidence: 99%